Pelatihan Sistem Cloud Computing Menggunakan Layanan Dropbox Bagi Mahasiswa Baru - Saputra, Gilang; Prasetyo, Muhammad Rasyid; Maulana, Farrel Rizqullah Ilham; Ikhsan, Teguh Pribadi (Universitas Wijaya Kusuma Surabaya, 2025)
Cloud computing is a combination of computer technology and internet-based development. Cloud computing uses the term